Successful service with SUKSIS - Pusat Bahasa Moden & Sains Kemanusiaan, . (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
10 May 2010. Centre for Modern Languages & Human Sciences (CMLHS), UMP recently spearheaded 100 UMP SUKSIS Corp during an Educational Community Service Programme (Program Khidmat Masyarakat & Pendidikan) at Kampung Tekek, Kampung Paya and Kampung Genting, Pulau Tioman.